Democracy in Arab universities. Issue 3 (3rd July 2017) - Saidani, Mounir
ABSTRACT: The procedural concept of university democracy as relying on an existing customary or written law that guarantees a real, forthright, integral system of power and counter-power that can ensure the widest participation for all stakeholders in the management of university affairs, and in the management of the symbiotic relationship between the university and its social environment, was adopted for this study. In an attempt to measure the presence of democracy in the discourses, practices, courses and education curricula of 36 Arab universities in 18 Arab countries, the study was based on the findings of a survey collected on the discourses of the universities in question. Analytical material that detailed and documented examples of each of the 'connotations on democracy' was scrutinized. Conclusions show the 'weakness' to 'no presence' of democracy in some Arab universities' curricula, programmes and courses. This may not be the result of a premeditated planning strategy, but rather one that is undoubtedly absent on coordination between the discourse of university leaders and the spread of the democracy in its meaning, behaviour and ethics within college life activities and course contents. In addition, there are forces that hinder democratic practice within the very university institutions that host democratic practice incentives. Analysis of both internal and external environments indicates an emphasis on the negative and stringent resistance to evolution by a large proportion of teachers, along with resistance to change in leaders.